MICROCLIMATE STUDIES IN THE YUKIDORI VALLEY, LANGHOVDE, ANTARCTICA IN 1988-1989 (EXTENDED ABSTRACT) (Twelfth Symposium on Polar Biology) - オオタニ, シュウジ; カンダ, ヒロシ; イノ, ヨシオ; OHTANI, Shuji; KANDA, Hiroshi; INO, Yoshio (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper